Significados e repercussões do câncer de próstata para um grupo de homens - Ferrão, Luana (2016)
The population aging it s a challenge for the society and the healthcare professionals. Along with the aging people can be tormented by chronic diseases and among them, cancer. The prostate cancer is an example in which age is an important risk, because its occurrence and mortality increases after the age of 50. The present dissertation is structured with a scientific production named Experiences of men with prostate cancer . It is a descriptive exploratory study with qualitative approach developed with 30 men carriers of prostate cancer undergoing oncologic treatment in a major port hospital from the north of Rio Grande do Sul (RS). The objective was to recognize the impact of diagnosis and the repercussions of prostate cancer to men in oncologic treatment. The samples were collected through semistructured interview, in the months of March to April 2015. From the participants, 24 were married, 4 were widowers and two were singles; in the 60-82 age group; the education has varied from incomplete elementary school to incomplete higher school. The agriculture was mentioned as occupation, by the majority of the participants. All belonging to cities of the 6ª Coordenadoria Regional de Saúde (Regional Health Coordinating RHC) in the north of RS. The thematic review allowed the construction of four categories: Impact of diagnosis and its confrontation; the compromised sexuality in the therapeutic way; and urinary incontinence and the repercussions in the daily routine of the men. So, there is a need in development of strategies and actions to improve quality of life of the prostate cancer patients